РОЗВИТОК КРАЄЗНАВЧОГО РУХУ НА ПОДІЛЛІ У ДРУГІЙ ПОЛОВИНІ XIX - ПОЧАТКУ XX СТОЛІТТЯ (Педагогіка вищої та середньої школи, 2007)
In the article gives an attempt to determine the place of some personalities in the process of development of the musical folklore study, examines their personal contribution into the music life of Podillia of the XIX c. — beginning of the XX c.